Activities and sources of income after a period of long-term sick leave - a population-based prospective cohort study - Wikman Anders; Wiberg Michael; Marklund Staffan; Alexanderson Kristina (BMC, 2012)
Abstract Background There is limited knowledge about what happens to people after long-term sick leave. The aim of this report was to conduct a prospective study of individuals who were on prolonged sick leave during a particular year, considering their activities and sources of income during subsequent years. To enable comparison of different time periods, we used three cohorts of individuals with different starting years. Methods Using data from national registers, three separate cohorts were constructed that included all people living in Sweden who were 20-64 years of age (>5 million) in the years 1995, 2000 and 2005, respectively. The individual members of the cohorts were classified into the following groups based on their main source of income and activity in 1995-2008: on long-term sick leave, employed, old-age pensioner, long-term unemployed, disability pensioner, on parental leave, social assistance recipient, student allowance recipient, deceased, or emigrated. Results Most individuals on long-term (> 6 months) sick leave in 1995 were not employed 13 years later. Only 11% of the women and 13% of the men were primarily in employment after 13 years. Instead, a wide range of alternatives existed, for example, many had been granted disability pension, and about 10% of the women and 17% of the men had died during the follow-up period. A larger proportion of those with long-term sick leave were back in employment when 2005 was the starting year for the follow-up. Conclusions The low future employment rates for people on long-term sick leave may seem surprising. There are several possible explanations for the finding: The disorders these people may have, might have entailed longstanding difficulties on the labor market. Besides, long-term absence from work, no matter what its causes were, might have worsen the chances of further employment. The economic cycles may also have been of importance. The improving labor market during later years seems to have improved the chances for employment among those earlier on long-term sick leave.